Peran Dan Tanggung Jawab Kepala Sekolah Dalam Pengelolaan Manajemen Perkantoran DI SD IT Zia Salsabila Bandar Setia - Salniati Nasution; Lili Raflika; Tengku Darmansah; Fikri Hamdi Siregar (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to examine the role and responsibilities of the principal in managing office management at SD IT Zia Salsabila Bandar Setia. Through a mixed methodology approach, this research identifies that visionary leadership, effective communication and coordination, and good human resource management are key factors in successful office management. School principals are not only responsible for academic activities, but must also be able to manage resources efficiently, overcome challenges such as budget limitations, and ensure administrative procedures run smoothly. This research also highlights the importance of a participatory approach in decision making and the use of information technology to increase efficiency and reduce administrative workload. It is hoped that the recommendations provided can be implemented to improve the effectiveness of office management, which ultimately contributes to better achievement of educational goals. This research offers a theoretical contribution to the educational management literature and a practical guide that can be adapted by school principals in a variety of educational contexts.